5-3(x+3)=-2(5x+2

Simple and best practice solution for 5-3(x+3)=-2(5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(x+3)=-2(5x+2 equation:



5-3(x+3)=-2(5x+2
We move all terms to the left:
5-3(x+3)-(-2(5x+2)=0
We multiply parentheses
-3x-(-2(5x+2)+5-9=0

See similar equations:

| 6/n=3/56 | | -8=-7k+8k | | 8f-19=12f-6f+17 | | x+16+x-12=90 | | 20=5+0.5d | | 3=m-3-2 | | -15x+136=121 | | 7+6k-4K=-5 | | -15+136x=121 | | -17+16r-20=11r-2 | | x−212=425 | | 2(2z-3)=6(4+3) | | x+16+x-14=90 | | x^2=28x-49 | | 2(2z03)=6(4+3) | | 12g=(8g-12)+11 | | 12g=12(8g-12)+11 | | 35=7.5+1/4x | | -21=3k+4k | | -15+150x=135 | | 3k+4+7=23 | | 6k+2+3k=9k+2 | | 3x+9+x-11=90 | | 35=5+2.50+1/4x | | 5.4-6x= | | -19=-4n-2+3 | | 4x=48-2x^2 | | 12h+6-4h=9h+2 | | 12x^2-140+300=0 | | 4x=48-2 | | 7.6x7.6=57.76 | | 7(7x+8)=448 |

Equations solver categories